My book of Dinosaurs and Prehistoric Life - Lomax; Dean (Britain DK (Dorling Kindersley), 2005)
e first living cells to fearsome dinosaurs and giant mammals, take a journey through prehistory to find out about the supersized, the scary, and the downright bizarre animals and plants that inhabited Earth in ancient times. Broken down by animal or plant type, there are profiles on more than 40 key species. With famous favorites such as mighty Tyrannosaurus and huge woolly mammoths, as well as lesser-known organisms, including five-eyed Opabinia and aeroplane-sized pterosaur Quetzalcoatlus, children won't fail to be captivated by the amazing range of beasts on display. Learn about the primeval world itself and how the Earth has changed over time, why fossils form, and the arrival of early humans. Detailed artworks bring the past to life, while pronunciation guides help with tricky names, and a visual index provides a quick overview of every species in the book. My Book of Dinosaurs and Prehistoric Life is an ideal first book about early plants and animals, and is sure to be a hit with fact-obsessed young fans of all things dinosaurs and other prehistoric life